Design and Development of an Interactive Persuasive Mathematics Game for Primary School Children - Moosa Qasim, Mustafa; Sadiq Khalaf, Hussein; Raad Abdulkareem, Ali; Md. Yussop, Yussalita (International Journal of Engineering and Technology, 2018)
It is a well-known fact in most countries of the world that primary school students do not favour mathematics. They are always subjected to high level of anxiety. This condition is clearly seen among Malaysian’ primary school students and this might have a substantial impact on their understanding of mathematics. Furthermore, this is also known as the pathological fear which is considered infectious and normally extends to other subjects related to mathematics. This paper discusses the anxiety as a hindrance factor in resulting poor performance in mathematics. To remedy this problem, this paper introduces the digital wayang kulit (DWK) characters originate from the traditional Malay theatre as a motivational platform for primary school students to overcome their anxiety towards mathematics. Finally, recommendations are introduced to design a persuasive mathematics game using DWK to help primary school students in learning and improving their mathematics skills in the future. Finally, this paper proposes the design of interactive persuasive mathematics game using DWK to help elementary students in learning and improving their mathematics skills.